PENGARUH MEDIA KANTONG PERKALIAN TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II MATERI OPERASI PERKALIAN DI SDN MARGOMULYO lV - Arik Sabela; Uci Ulfa Nur’afifah; Desi Nuzul Agnafia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the effect of multiplication pocket media on second-grade students’ mathematics learning outcomes at SDN Margomulyo IV. The background of this research stems from the observation that students’ performance in multiplication operations was below the minimum mastery criteria due to the lack of varied and interactive teaching media. This quantitative study used a one-group pretest-posttest design, involving 20 students as both the population and sample. Data were collected using a multiple-choice test consisting of 20 items administered before and after the intervention. The instrument was validated through expert judgment and statistical tests using SPSS 24. Analysis of the results indicated that the average pretest score was 58.50, which increased to 76.50 in the posttest. The normality test showed a significance value of 0.159 for the pretest and 0.071 for the posttest, both greater than 0.05, indicating normally distributed data. The paired sample t-test resulted in a significance value of 0.000 < 0.05, confirming a significant effect of the multiplication pocket media on student learning outcomes. These findings suggest that the use of interactive and tangible teaching aids, such as multiplication pockets, can significantly enhance students’ understanding and achievement in learning multiplication.